Child Protection from Online Grooming in Indonesian Criminal Law - Fadli Yasser Arafat Juanda; M Zaldy (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Online grooming of children has emerged as one of the most alarming manifestations of digital sexual exploitation, yet Indonesia's criminal law framework has been slow to address it coherently. This study examines whether four major Indonesian criminal law instruments, the Child Protection Act (Law No. 35 of 2014), the Electronic Information and Transactions Act (Law No. 19 of 2016), the Sexual Violence Crimes Act (Law No. 12 of 2022), and the National Penal Code (Law No. 1 of 2023), are adequate to criminalize and prosecute online grooming behavior against children. Employing a normative legal research design with statute and conceptual approaches, this study analyzes primary legal materials and international instruments to identify normative gaps. The findings reveal three critical deficiencies: the absence of a statutory definition of grooming, incomplete coverage of preparatory acts as independent criminal offenses, and inadequate cross-sectoral coordination mechanisms. While the Sexual Violence Crimes Act and the National Penal Code represent meaningful legislative progress, neither fully incorporates online grooming as a distinct, standalone criminal offense. This study recommends targeted legislative amendments and enhanced implementation protocols to align Indonesia's criminal law framework with its obligations under the Convention on the Rights of the Child and international child protection standards.